Spontaneous rupture of the branches of left subclavian artery: A case report and review of the literatures. Issue 14 (April 2018) - Tong, Ya-Ling; Lu, Yuan Qiang; Jiang, Jiu-Kun; Chen, Nai Yun; Xu, Jia
Abstract: Rationale: Spontaneous rupture of the branches of left subclavian artery (LSA) without any obvious risk factors is rare. Patient concerns: A 51-year-old female patient without history of trauma and hypertension complained about left chest pain. Diagnoses: A chest Computed tomography (CT) scan revealed a large pleural effusion (PE) in the left thorax cavity and hemothorax was confirmed by thoracentesis. Interventions: The patient underwent surgery. Outcomes: spontaneous rupture of the branches of LSAwas confirmed. Lessons: The patient recovered well and discharged after timely treatments. The unusual possibility should be paid attention in mind in acute chest pain cases.